2021
DOI: 10.3390/ma14020303
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study on Processing Ti–6Al–4V ELI with High Power EDM

Abstract: Electrical Discharge Machining (EDM) consists of a non-conventional machining process, which is widely used in modern industry, and especially in machining hard-to-cut materials. By employing EDM, complex shapes and geometries can be produced, with high dimensional accuracy. Titanium alloys, due to their unique inherent properties, are extensively utilized in high end applications. Nevertheless, they suffer from poor machinability, and thus, EDM is commonly employed for their machining. The current study prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…To improve machining, one effective method is to add nano-powders to the dielectric fluid in the proper quantity [ 17 , 18 ]. By enhancing spark discharge, the particle’s inclusion in the dielectric fluid lowers the breakdown strength and enhances the igniting mechanism [ 19 ]. In turn, this improves the process’s capacity for cutting.…”
Section: Introductionmentioning
confidence: 99%
“…To improve machining, one effective method is to add nano-powders to the dielectric fluid in the proper quantity [ 17 , 18 ]. By enhancing spark discharge, the particle’s inclusion in the dielectric fluid lowers the breakdown strength and enhances the igniting mechanism [ 19 ]. In turn, this improves the process’s capacity for cutting.…”
Section: Introductionmentioning
confidence: 99%
“…Karmiris-Obrataski et al [20] used a graphite electrode and a high-power EDM during the processing of material Ti-6Al-4V ELI. ANOVA model revealed that both the pulseon time and current have a strong influence on the MRR with contributions of 61.65% and 21.94%, and provided some combinations of machining parameters that result in a lower TWR and thus lower machining costs, making the machining economically feasible.…”
Section: Titanium Alloy and Cutting Tool Materialsmentioning
confidence: 99%
“…As a result of which, the electrical energy is converted into heat energy. The temperature attained on the surface of the material where the spark hits, is of the order of 6,000-12,000ºC has identi ed by Karmiris-Obratanski et al [4]. As a result of which some part of the material is melted and evaporated.…”
Section: Introductionmentioning
confidence: 96%